Analisis Pelatihan dan Kompensasi terhadap Kinerja Karyawan Melalui Kepuasan Kerja Sebagai Variabel Intervening pada PT. Anugrah Harapan Nusantara - Emil Salim; Kusuma Chandra Kirana; Henny Welsa (Universitas Batanghari, 2022)
The purpose of this study was to analyze the effect of training to job satisfaction; the effect of compensation to job satisfaction; the effect of training to employee performance; the effect of compensation to employee performance; the effect of training to employee performance through job satisfaction; the effect of compensation to employee performance through job satisfaction. This research was located in Gowa Regency involving employees of PT Anugrah Harapan Nusantara. The sampling technique used Saturated Sampling method. Data analysis used in this research were descriptive analysis, inferensial analysis, and mediation analysis. The analysis tool in this research was the Partial Least Square (PLS) analysis with SmartPLS 3.2.8 software, and the mediation analysis used the Bootstrapping. The results of the analysis on hypothesis testing in this study indicate that training has a positive and significant effect to job satisfaction; compensation has a positive and significant effect to job satisfaction; training has a positive and significant effect to employee performance; compensation has a positive and significant effect to employee performance. The results of the bootstraping test on mediation analysis show that training has a positive but not significant effect to employee performance through job satisfaction; compensation has a positive and significant effect to employee performance through job satisfaction.